Pengaruh Pengalaman Mengajar Dan Disiplin Kerja Terhadap Prestasi Kerja Guru Yang Dimediasi Oleh Profesionalisme (Studi Pada Guru SMPI Miftahul Ulum Tambelengan Kabupaten Sampang) - Ali Wafa; Rudi Winarko; Chamariyah Chamariyah (Journal of Management and Creative Business, 2023)
Aliwafa, 2023. The Effect of Teaching Experience and Work Discipline on Teacher Work Performance Mediated by Professionalism (Study on SMPI Miftahul Ulum Tambelengan teachers, Sampang Regency), Wijaya Putra University Postgraduate Program. This type of research is explanatory, namely to test the hypotheses between the hypothesized variables that will be tested for truth. the research approach used is quantitative, the research sample is 61 respondents. Data analysis used SPSS analysis and PLS Program SEM analysis. The aims of this study were: 1) to test and analyze whether teaching experience has a direct effect on teacher performance at SMPI Miftahul Ulum Tambelengan, Sampang Regency; 2) To test and analyze whether work discipline has a direct effect on teacher performance at SMPI Miftahul Ulum Tambelengan, Sampang Regency; 3) To test and analyze whether teaching experience has a direct effect on the professionalism of SMPI Miftahul Ulum Tambelengan teachers, Sampang Regency; 4) To test and analyze whether work discipline has a direct effect on the professionalism of SMPI Miftahul Ulum Tambelengan teachers, Sampang Regency; 5) To test and analyze whether professionalism has a direct effect on teacher performance at SMPI Miftahul Ulum Tambelengan, Sampang Regency; 6) To test and analyze whether teaching experience has an indirect effect on teacher performance at SMPI Miftahul Ulum Tambelengan, Sampang Regency, which is mediated by professionalism; 7) To test and analyze whether work discipline has an indirect effect on teacher performance at SMPI Miftahul Ulum Tambelengan, Sampang Regency, which is mediated by professionalism. The results of the study show that: 1) Teaching experience has a direct effect on teacher performance at SMPI Miftahul Ulum Tambelengan, Sampang Regency, with an original sample value of 0.451 and a p-value of 0.000; 2) Work discipline has a direct effect on teacher performance at SMPI Miftahul Ulum Tambelengan, Sampang Regency, with an original sample value of 0.199 and a p-value of 0.037; 3) Teaching experience has a direct effect on teacher professionalism at SMPI Miftahul Ulum Tambelengan, Sampang Regency with an original sample value of 0.509 and a p-value of 0.000; 4) Work discipline has a direct effect on teacher professionalism at SMPI Miftahul Ulum Tambelengan, Sampang Regency, with an original sample value of 0.251 and a p-value of 0.038; 5) Professionalism has a direct effect on teacher performance at SMPI Miftahul Ulum Tambelengan, Sampang Regency with an original sample value of 0.267 and a p-value of 0.011; 6) Teaching experience has an indirect effect on teacher performance at SMPI Miftahul Ulum Tambelengan, Sampang Regency, which is mediated by professionalism with an original sample value of 0.136 and a p-value of 0.035; 7) Work discipline has an indirect effect on teacher performance at SMPI Miftahul Ulum Tambelengan, Sampang Regency, which is mediated by professionalism with an original sample value of 0.067 and a p-value of 0.013.